Cyanobacterial flora in some salt pans of Pudukkottai District, TamilNadu, India - S. Manokaran, T. Nedumaran (Journal of Phytology, 2009)
The present study was conducted diversity of Cyanobacterial flora in the salt pans of Kattumavadi, Prathaparamanpattinam, Manamelkudi and Ammapattinam located in Palk bay and Palk strait during the summer season 2008. A total number of 25 cyanobacterial species were collected 11 of Oscillatoriaceae 6 Chroococcaceae 5 Nostocaceae and 3 each of Scytonemataceae, Rivulariaceae and Stigonemataceae, Physico-chemical parameters were also studied.